PENGARUH SEPEDA MOTOR TERHADAP KAPASITAS PENDEKAT PADA SIMPANG BERSINYAL LENGAN JALAN S. PARMAN-LENGAN JALAN SUTOYO SIMPANG SKIP KOTA BENGKULU - Fatmawati Fatmawati; Hardiansyah Hardiansyah; Yuzuar Afrizal (Inersia: Jurnal Teknik Sipil, 2019)
This research is made to find out starting time deprivation of green which caused by motorcycle s and their effect toward capacity on S. Parman road and Sutoyo Simpang Skip rapprochement in Bengkulu. The research was doing in three days on Sunday, Monday, and Wednesday, each of the date was on March 10th, 18th, and 20th 2013. Further, it uses calculation based on Manual Kapasitas Jalan Indonesia (MKJI, 1997) data. Thereby, the results are 1.67 second for the lowest starting time deprivation of green and 12.263 % for the highest increasing capacity on Sunday in the end of afternoon. In line, others are 1.49 second for the lowest of starting time deprivation and 13.21 % for the highest increasing capacity on Sunday in daylight. In the end, this deprivation caused by motorcycles, causes capacity change, deprivation got smaller when the capacity increased. In contrast, it’s better when starting time deprivation of green got higher and the increasing capacity got lower.